(untitled) (CommonHealth, 2021)
Child sexual abuse recurrence can have a detrimental and devastating effect on victims. Less is known, however, about the risk and protective factors associated with child sexual abuse recurrence. In order to better understand these risk and protective factors, a narrative review was conducted of the current literature. Academic databases, cited references, and reference lists were searched for peer-reviewed research that focused on sexual abuse recurrence prior to age 18 years. The risk and protective factors identified in the literature were organized into four a priori categories based on an ecological systems framework: child, characteristics of the maltreatment, family, and community/social systems. Examples of risk factors at each level were child mental health concerns (child), the perpetrator being the mother’s significant other (characteristics of the maltreatment), parental history of sexual abuse (family), and active or prior child welfare involvement (community/social systems). Only two protective factors were identified, both regarding the family: family social support and a parent believing the child’s report of the initial victimization. There were mixed or inconclusive findings for several factors. Overall, the review indicates that tertiary prevention, including child-, caregiver-, and perpetrator-focused strategies, should be employed to mitigate the risk factors and enhance the protective factors for child sexual abuse recurrence. Further research is needed to address protective factors and community/social systems factors and could, building on this narrative review, involve a systematic review of the child sexual abuse recurrence literature.